Surgical Strategies to Reduce Postoperative Recurrence of Crohn's Disease After Ileocolic Resection - Reynolds, Ian S.; Doogan, Katie L.; Ryan, Éanna J.; Hechtl, Daniel; Lecot, Frederik P.; Arya, Shobhit; Martin, Sean T. (Frontiers in Surgery, 2021)
Postoperative recurrence after ileocaecal resection for fibrostenotic terminal ileal Crohn’s disease is a significant issue for patients as it can result in symptom recurrence and requirement for further surgery. There are very few modifiable factors, aside from smoking cessation, that can reduce the risk of postoperative recurrence. Until relatively recently, the surgical technique used for resection and anastomosis had little or no impact on postoperative recurrence rates. Novel surgical techniques such as the Kono-S anastomosis and extended mesenteric excision have shown promise as ways to reduce postoperative recurrence rates. This manuscript will review and discuss the evidence regarding a range of surgical techniques and their potential role in reducing disease recurrence. Some of the techniques have been shown to be associated with significant benefits for patients and have already been integrated into the routine clinical practice of some surgeons, while other techniques remain under investigation. Current techniques such as resection of the mesentery close to the intestine and stapled side to side anastomosis are being challenged. It is looking more likely that surgeons will have a major role to play when it comes to reducing recurrence rates for patients undergoing ileocaecal resection for Crohn’s disease.